2021
DOI: 10.1016/j.ijid.2021.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Staphylococcus aureus nasal carriage and surgical site infection rate among patients undergoing elective cardiac surgery

Abstract: Background: Nasal carriers of Staphylococcus aureus are at increased risk of postoperative surgical site infection. Nasal decolonization with mupirocin is recommended in patients undergoing cardiac surgery to reduce surgical site infection. These data are still lacking in Thailand. Therefore, the aim of this study was to determine the prevalence of S. aureus nasal carriage in Thai patients undergoing elective cardiac surgery. The association of surgical site infection and S. aureus nasal carriage was also exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Although this study was conducted in tertiary hospital hemodialysis centers, we did not find MRSA. This conforms with reported data in Thailand which indicated an extremely low rate of MRSA nasal colonization either among patients or healthcare personnel [ 13 , 14 , 17 ]. The molecular basis and biofilm-forming capacity of S. aureus in each strain play a major role in the ability to colonize and develop invasive diseases [ 2 , 26 – 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although this study was conducted in tertiary hospital hemodialysis centers, we did not find MRSA. This conforms with reported data in Thailand which indicated an extremely low rate of MRSA nasal colonization either among patients or healthcare personnel [ 13 , 14 , 17 ]. The molecular basis and biofilm-forming capacity of S. aureus in each strain play a major role in the ability to colonize and develop invasive diseases [ 2 , 26 – 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, the prevalence of S. aureus nasal carriage in the general population in Thailand is low. Related studies in Thailand reported the prevalence of S. aureus nasal carriage at 20, 13.9, and 3.6% among patients with allergic rhinitis, patients undergoing elective cardiac surgery, and pre-admission screening, respectively [ 12 14 ]. These proportions are lower than the reported prevalence in the US and Germany at 22% and 40%, respectively [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was conducted in tertiary hospital hemodialysis centers, we could not nd MRSA. This conforms with the related data in Thailand which indicated an extremely low rate of MRSA nasal colonization either among patients or healthcare personnel [13,14,17]. The molecular basis of S. aureus in each strain plays a major role in the ability of colonization and developing invasive diseases [2].…”
Section: Discussionsupporting
confidence: 85%
“…Firstly, the prevalence of S. aureus nasal carriage in the general population in Thailand is low. Related studies in Thailand reported prevalence of S. aureus nasal carriage at 20, 13.9, and 3.6% among patients with allergic rhinitis, patients undergoing elective cardiac surgery, and pre-admission screening, respectively [12][13][14]. These proportions are fewer than the reported prevalence in the US and Germany at 22% and 40%, respectively [4,15].…”
Section: Discussionmentioning
confidence: 99%